Ailanthone induces apoptosis in U-2OS cells through the endoplasmic reticulum stress - Zhang, Yue; Wu, Taiding; Li, Chang; Luo, Nianfang; Wang, Jun; Li, Jingxian; Tian, Min; Liu, Lei; Li, Ruiting; Zhang, Jingyi (Frontiers in Immunology, 2025)
BackgroundOsteosarcoma (OS) is a malignant bone tumor that commonly occurs in children and adolescents, characterized by poor treatment outcomes and prognosis, highlighting the urgent need for alternative therapies. Endoplasmic reticulum stress (ERS) induces a series of cascade reactions known as the unfolded protein response (UPR), which is a crucial stress mechanism that cells utilize to cope with disrupted endoplasmic reticulum function and is widely involved in the apoptosis of tumor cells. Excessive UPR can lead to an overload of protein levels within cells, disrupting homeostasis and exhausting energy, ultimately inducing apoptosis in OS cells. Ailanthone (AIL), a natural compound derived from the root bark or stem bark of Ailanthus altissima (Mill.) Swingle, exhibits broad-spectrum anticancer activity across multiple tumor types. Its antitumor mechanism involves the modulation of endoplasmic reticulum stress (ERS)-associated proteins, including the upregulation of apoptotic markers (PERK, eIF2α, ATF4, CHOP) and pro-apoptotic factors (BAX, caspase-3, Bim), alongside the downregulation of the anti-apoptotic protein BCL-2. This study aims to investigate whether AIL induces apoptosis in OS cells via ERS.Materials and methodsThe effects of AIL (0-1.0 µmol/L) on the proliferation and migration of U-2OS cultured for 24 h were evaluated using the cell counting kit-8 assay and scratch wound healing assays. The optimal concentration of 0.6 µmol/L was selected for subsequent experiments. Western blot analysis was performed to measure the protein levels of ERS-related factors at different time points (0–24 h) following AIL treatment. Finally, the apoptosis rate of U-2OS cells after 24 h of culture at the optimal concentration was assessed by flow cytometry.ResultsAIL exhibited a dose-and time-dependent inhibitory effect on U-2OS cell growth, significantly reducing cell proliferation and migration rates while promoting apoptosis. After AIL treatment, the levels of ERS-related proteins and pro-apoptotic proteins increased, while anti-apoptotic protein level decreased.ConclusionAIL inhibited the proliferation of human OS cells and induced apoptosis through the ERS pathway. It represented a potential therapeutic agent for OS treatment.